Bulk storage of "Wonderful" pomegranate fruit using modified atmosphere bags. Issue 1 (2nd January 2016) - Porat, Ron; Kosto, Itzhak; Daus, Avinoam
ABSTRACT: "Wonderful" pomegranates can be stored under modified atmosphere (MA) conditions for up to 3–4 months after harvest. Until recently, the harvested fruit first needed to be transferred to the packing house and packed in MA bags in cartons or plastic boxes before cooling to the desired temperature and subsequent cold storage. During the last few years, together with StePac Ltd, we have developed a new methodology in which "Wonderful" pomegranate fruit are directly harvested into large 80 kg or even 320 kg bulk X tend® MA bags in harvest bins, and then immediately transferred from the field to commercial cold storage rooms without the necessity of repacking the fruit at the packing house. In this study, we evaluated the postharvest storage performance and fruit quality of "Wonderful" pomegranates stored in bulk 80 kg X tend® MA bags in harvest bins for various periods of 4, 8, 12, and 16 weeks at 7 °C followed by 1 week in shelf life conditions at 20 °C. The results show that "Wonderful" pomegranates can be maintained in bulk X tend® MA bags in harvest bins at excellent quality with minimal losses for at least 12 weeks after harvest. Overall, this new suggested procedure allows direct transfer of large volumes of fruit from the field to cold storage rooms without intermediate transferring to the packing house, thus saving precious time and extra packaging and labor costs, and ensuring better maintenance of the cold storage chain.